Algorithms - Sedgewick, Robert; Wayne, Kevin Daniel (Upper Saddle River, NJ : Addison-Wesley, 2011)
The book surveys the most important computer algorithms in use today, and teaches fundamental techniques to the growing number of people in need of knowing them.
Includes index.
rua 30/10/13
Loans
Keywords: Computer algorithms; Algorithms